High HIV, HPV, and STI Prevalence Among Young Western Cape, South African Women: EVRI HIV Prevention Preparedness Trial. (1st February 2015) - Giuliano, Anna R.; Botha, Matthys H.; Zeier, Michele; Abrahamsen, Martha E.; Glashoff, Richard H.; van der Laan, Louvina E.; Papenfuss, Mary; Engelbrecht, Susan; Schim van der Loeff, Maarten F.; Sudenga, Staci L.; Torres, Benji N.; Kipping, Siegfried; et al.
Abstract : Background: This study sought to assess the feasibility of conducting a phase III HIV prevention trial using a multivalent human papillomavirus (HPV) vaccine (Gardasil; Merck, Whitehouse Station, NJ). Methods: A total of 479 sexually active women aged 16–24 years in the Western Cape, South Africa, were enrolled in the Efficacy of HPV Vaccine to Reduce HIV Infection (EVRI) Trial. Of these, 402 were HIV negative, nonpregnant, and randomized 1:1 to receive Gardasil or a saline placebo vaccine. Vaccine doses were administered at enrollment, month 2, and month 6, and participants were followed for 1 month after the third dose. Enrollment HIV, HPV, other sexually transmitted infections (STIs), and cervical cytology were evaluated. Rates of accrual, vaccine compliance, and adherence to protocol were monitored. Results: High rates of accrual of eligible females to study (93%) and completion of the 3-dose vaccine series (91%) were noted, with few protocol violations. Ineligibility due to reported HIV positivity was 19%, and another 12% of those enrolled tested HIV positive. STI prevalence was high, with 6.2%, 10.9%, and 32.8% testing positive for syphilis, gonorrhea, and chlamydia, respectively. Cervical prevalence of ≥1 of 37 HPV types was 71%. STI and HPV prevalence was highest among the youngest women (<19 years). Conclusions: Feasibility (successful accrual, retention, and vaccination) of conducting randomized placebo-controlled trials of HPV vaccines among HIV high-risk women in South Africa was demonstrated. This work demonstrates that phase III HIV prevention trials need to intervene at young ages and screen and treat multiple STIs concurrently to have a measurable impact on HIV acquisition. Abstract : Supplemental Digital Content is Available in the Text.